Relationship Between Balanced Nutritional Behavior and the Occurrence of Hypertension on the Lances in Puskesmas Sabbang Paru (Comprehensive Health Care, 2024)
Hypertension in elderly is mostly isolated systolic hypertension (HST), increasing systolic pressure leads to increasing risk of stroke and myocardial infarction even if the diastolic pressure is within normal limits. (isolated systolic hypertension). The aim of this study is to find out the relationship between balanced nutritional behavior and the occurrence of hypertension in the elderly. The type of research used is quantitative with a cross sectional study approach. The population in this study is the entire elderly suffering from hypertension aged 60-74 years in the Puskesmas Sabbangparu Lung Working Region with a total of 32 respondens. The sample in the study is 32 respondens. The results of the study show that the most balanced nutritional behaviour is the most dominant category as many as 30 (93.8%) respondents. while, the remainder of respondents with poor balanced dietary behavior as much as 2 (6.3%) respondents. Pearson Chi square results obtained a value ρ = 0,004 This indicates that ρ< α (α=0,05) then Ha is accepted and H0 rejected. The conclusion of this study is that the most dominant nutritional behavior is a good category. The most prevalent occurrence of hypertension is a stage II category.